White Paper: Clinical Studies in Radiology - Antoch, G.; Barkhausen, J.; Düber, C.; Epsch, R.; Heindel, W.; Krombach, G.; Maintz, D.; Schlemmer, H. P.; Schönberg, S.; Wigge, P. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Citation Format:• G. Antoch, J. Barkhausen, C. Düber, R. Epsch, W. Heindel, G. Krombach, D. Maintz, H. P. Schlemmer, S. Schönberg, P. Wigge. White Paper: Clinical Studies in Radiology. Fortschr Röntgenstr 2014; 186: 451 – 457